Impact of Management Authority Transfer of SMA/SMK from Regency/City Government to Provincial Government in West Kalimantan - Hamid Darmadi (JETL (Journal of Education, Teaching and Learning), 2019)
The purpose of this study is to obtain objective information and clarity regarding the impact of management authority transfer of senior high school (SMA)/vocational high school (SMK) from regency/city government to the provincial government in West Kalimantan Province. The benefit of the results theoretical and practical for teachers, school principals, education and culture services and regional governments. The population in this study were SMA/SMK teachers, SMA/SMK principals, regency/city education office and the provincial education office of West Kalimantan. This study uses direct communication techniques, direct observation techniques, and documentation techniques. The results of this study indicate that: (1) Management of SMA/SMK by the regency/city government and school activities run smoothly before the authority transfer of SMA/SMK to the Provincial Government Staffing. There is no separation between elementary school, junior school, high school and vocational school by Regency/City Education Service; (2) Management of SMA/SMK after the transfer of authority by the provincial government is obtained data and information there is a tendency for SMA/SMK to be abandoned by Regency/City Education Services because they are not responsible anymore to take care of SMA/SMK, while the Provincial Education Service which has the mandate to take care of SMA/SMK is difficult to reach schools, especially SMA/SMK far in remote areas, outermost, disadvantaged and remote areas; (3) The workload of the Head of Regency/City SMA/SMK Court MKKS after the transfer of management of SMA/SMK to the province is felt to be increasingly heavy. Because the duties of the School Supervisor that should be handled by the SMA/SMK Supervisor cannot be implemented properly due to the limited budget of the visit, the location of the SMA/SMK is too far away. Finally, the task of the School Supervisor was forced to be taken over by the Chairperson of the Regency/City MKKS. Even to the extent that the selection of selected SMA/SMK principals is conducted by the Chairperson of the MKKS.